Real-Time and In Situ Evaluation of Phycocyanin Concentration in Spirulina platensis Cultivation System by Using Portable Raman Spectroscopy - Yong He; Xiaoxi Liu; Hui Fang; Jinnuo Zhang; Xuping Feng (Journal of Chemistry)
Spirulina platensis can synthesize a large amount of phycocyanin, which had been developed as a health food. At the same time, Spirulina can absorb the nitrogen and phosphorus in wastewater and provide for its own growth. Here, we studied the optimal nitrogen and phosphorus supply for the Spirulina production process. For the first time, 405 nm portable Raman spectrometer was used to estimate phycocyanin content for real-time industrial applications. We obtained three Raman characteristic peaks of phycocyanin through density functional theory combined with home-built Raman spectrometer, which were 1272, 1337, and 1432cm−1. There was a good linear correlation between the sum of the three peak intensities and the PCL concentration (y = 18.887x + 833.530, R2=0.890). The least squares support vector machine model based on the characteristic peaks was used to estimate the concentration of phycocyanin and obtained good results with a correlation coefficient of prediction of 0.907 and residual predictive deviation of 3.357. The results can provide decision-making for integration of Spirulina effluent treatment and phycocyanin production and provide references for real-time Spirulina-based biorefinery applications.